Phenotype and genotype characterisation of macrolide, lincosamide and streptogramin B resistance among Hospital and community isolated staphylococcus aureus strains - El Kammoshi, Asma Mesbah (2016)
Staphylococcus aureus is an important cause of nosocomial and community-acquired infections in every region of the world. The success of S. aureus as a pathogen and its ability to cause such a wide range of infections is due to its extensive virulence factors. The increase in the resistance of this virulent pathogen to antibacterial agents, coupled with its increasing prevalence as a nosocomial pathogen, is a cause for consternation. The escalating frequency of S. aureus infections and the changing patterns in antimicrobial resistance have led to renewed interest in the use of macrolide lincosamide–streptogramin B (MLSв) antibiotics to treat such infections. Therapeutic failure to clindamycin has been reported due to mechanisms which confer resistance constitutively, or by the presence of low level inducers. Clindamycin is one of the alternative agents used to treat S. aureus infections and accurate identification of clindamycin resistance is important to prevent therapeutic failure. Unfortunately, inducible clindamycin resistance is not detected by standard susceptibility tests. Also, the incidence of drug-resistant pathogens differs greatly between countries according to differences in the usage of antibiotics. This research was carried out in order to study the prevalence of iMLSв in community associated (CA) and hospital associated (HA) S. aureus isolates from clinical samples, and for the presence of macrolide and lincosamides resistance genes [erm(A), erm(B),erm(C)and msr(A)]. A total of 133 and 50 isolates of clinical and community acquired samples,respectively were obtained from various sites. Disk diffusion testing by placing clindamycin and erythromycin disks 15 mm and 26 mm apart (edge to edge) on a Mueller-Hinton agar, as per CLSI guideline and E-test methods were performed. The result showed that only four out of 183 (2.2%) clinical isolates were resistant to erythromycin. Of these four isolates, one (25%) showed MS phenotype (erythromycin resistance; clindamycin susceptible) with msr(A) gene detected and the remaining three (75%) isolates exhibited D-phenotype (erythromycin resistance;clindamycin resistance) and positive for erm(C) gene. Similar findings were observed regardless of two different distances used for the screening of MLSв phenotypes. In addition, all 50 community isolates were sensitive to erythromycin and clindamycin. However, the isolates that showed MS phenotype and D-positive had different spa-types which show a diverse genetic heterogeneity. In spite of the low prevalence of S. aureus with iMLSв, it is quite interesting and significant to find that they were mostly isolated from inpatients. D-test becomes an imperative part of routine antimicrobial susceptibility test for all S. aureus isolates. Inducible clindamycin resistance testing should be done as a routine practice. Failure to inculcate this practice can lead to ineffective treatment options and ultimately irrational use of other higher class of antibiotics.